Medication Adherence and Self-Management Practices among Type 2 Diabetes Mellitus Patients in Jeli District, Kelantan, Malaysia - Muhammad, Marzuki bin; Yasmin, Farzana; Alabed, Alabed Ali A.; Abdullah, Bibi Florina; Poddar, Sandeep (Kesmas, 2022)
This study was carried out to investigate the level of medication adherence and diabetic knowledge among type 2 diabetes mellitus patients in Jeli District, Kelantan, Malaysia. This cross-sectional study was done from February to July 2019 by giving a questionnaire to 150 type 2 diabetes mellitus patients aged 40-80 years at three primary health cares in Jeli District, Kelantan, Malaysia. The quantitative descriptive method was used in this study. The findings of this study revealed that knowledge was significantly related to poor adherence. When sex, history of diabetes, and education were accounted for, patients with low diabetic knowledge had an odds ratio of 4.53 for poor adherence compared to those with high knowledge (adj 95% CI (1.92-10.69), p-value = 0.001). To achieve the goal of regulating diabetes management in primary health care, a clinical supervision program should be implemented to improve staff competence in diabetes management and to empower patients through self-management.